Traumatic pneumorrhachis with tension pneumocephalus - Pankaj Dawar; Gopal Sedain; Sumit Sinha (Indian Journal of Neurosurgery)
Air contained within the spinal canal is termed as pneumorrhachis. There are only few previously reported cases in the literature about pneumorrhachis. We herein report a case of pneumorrhachis associated with tension pneumocephalus in a patient with severe head injury.